Functional changes of Malaysia’s small towns in the era of globalization: evidences from Tanjong Malim, Perak - Yazid Saleh,; Mohmadisa Hashim,; Nasir Nayan,; Hanifah Mahat,; Mohamad Suhaily Yusri Che Ngah, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Economic globalization has paved the way for a greater concentration of modern economic activities in metropolitan cities. Development of manufacturing and office-based economic activities together with residential areas in turn have resulted in the metropolitan cities to grow in size and eventually led to the expansion of urban region incorporating the surrounding large and small towns. However, only towns located along the development corridors will be impacted by the prevailing process, leaving other settlements relatively untouched and stagnant. This study examined current functional changes characterizing small towns in Malaysia with particular reference to Tanjong Malim, Perak. Using data obtained through observations and a household survey, the study found that there was a significant change in the role of Tanjong Malim from mainly acting as a collecting center for agricultural products to a center of manufacturing and services that provided non-farm employment opportunities to its surrounding population. This change suggested that economically Tanjong Malim was growing and would continue to play an important role as a major development centre in Perak. The finding is an important indicator that a small town located outside the mainstream development corridor is capable of transforming its role from a traditional collection centre to a more modern manufacturing and service centre if properly planned. This finding also suggests that a small town can still play a significant role in the economic development of a country even in the era of globalization that often tends to favour metropolitan regions.